Adoption and Impact of Cooperation-88 Potato in China - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2018)
Potatoes have become increasingly popular amongst Chinese consumers, and the water saving and storage capacity of the crop have made it a target of Government promotions. Potato production is a means of generating income as well as improving food and water security. Getting the right varieties to Chinese farmers to meet the growing and changing consumer demands is thus important. In this analysis we track the impacts of a variety developed by CIP in partnership with Chinese researchers and find that tremendous benefits have been generated – and are still accruing. This brief reports the findings of a rigorous assessment of C88’s adoption and economic impacts. Researchers used household and community surveys to estimate current and historical adoption rates of C88, identify factors associated with its adoption (and disadoption), and assess the economic benefits of C88 diffusion to producers and consumers in Yunnan. This research was supported by ISPC-SPIA under the grant “Strengthening Impact Assessment in the CGIAR (SIAC) (https://cas.cgiar.org/spia/news/strengthening-impact-assessment-cgiar-siac-2013-2016).”